Bariatric Surgery and it Effects on the Respiratory System - Cherniack, E. P.; Cherniack, Neil S. (Current Respiratory Medicine Reviews, 2008)
Bariatric surgery for morbid obesity is an effective approach to weight loss in selected obese patients. The candidate for surgery must be massively obese and have failed to lose appreciable weight with diet, drugs, and exercise. He must also be committed to lifelong weight maintenance. Bariatric surgical procedures either limit the expansion of the stomach (restrictive surgery) or the effective mixing of gastric contents with bile and pancreatic enzymes (bypass surgery). Gastric bypass is the most commonly performed bariatric procedure in the United States. Bariatric surgery-induced weight loss is associated with improvements in cardiovascular respiratory, and metabolic function. Two recent studies have shown significant survival benefit for people who have bariatric surgery (most had restrictive surgery). However, bariatric surgery is risky with an appreciable perioperative mortality. Although bypass surgery usually produces more weight loss than restrictive surgery, it is associated with more complications caused by malabsorption of nutrients such as fat, protein, and fat soluble vitamins.